2017
DOI: 10.3389/fpsyg.2017.00001
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Spontaneous Expressive Suppression Predict Amygdala Responses to Fearful Stimuli: The Role of Suppression Priming

Abstract: Though the spontaneous emotion regulation has received long discussions, few studies have explored the regulatory effects of spontaneous expressive suppression in neural activations, especially in collectivistic cultural context. The functional magnetic resonance imaging (fMRI) study aimed to examine whether individual differences in the tendency to use suppression are correlated with amygdala responses to negative situations when individuals are unconsciously primed with expressive suppression. Twenty-three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
438
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 279 publications
(477 citation statements)
references
References 34 publications
(64 reference statements)
36
438
3
Order By: Relevance
“…However, we did not find this in the present study and instead found that the survivors showed lower prefrontal activation. A possible explanation of this incongruence could be that in the present study, the time elapsed from the traumatic event (about five years) could have facilitated the use of this distancing strategy with a lesser cognitive cost, as suggested by a recent study in which individuals with a higher unconscious and habitual use of suppression showed lesser amygdala activation in response to negative stimuli (Chen et al., ). Moreover, the lower intensity of the survivors’ prefrontal cortex found in the present study is consistent with that reported in previous studies in which the responsivity of this region has been shown to be inversely correlated with the performance of emotional cognitive tasks and symptom severity in a PTSD population (Lanius et al., ; Shin, Rauch, & Pitman, ).…”
Section: Discussionmentioning
confidence: 69%
“…However, we did not find this in the present study and instead found that the survivors showed lower prefrontal activation. A possible explanation of this incongruence could be that in the present study, the time elapsed from the traumatic event (about five years) could have facilitated the use of this distancing strategy with a lesser cognitive cost, as suggested by a recent study in which individuals with a higher unconscious and habitual use of suppression showed lesser amygdala activation in response to negative stimuli (Chen et al., ). Moreover, the lower intensity of the survivors’ prefrontal cortex found in the present study is consistent with that reported in previous studies in which the responsivity of this region has been shown to be inversely correlated with the performance of emotional cognitive tasks and symptom severity in a PTSD population (Lanius et al., ; Shin, Rauch, & Pitman, ).…”
Section: Discussionmentioning
confidence: 69%
“…Yet the Kuleshov “effect,” if it exists at all in this three‐shot format, does so only under extremely circumscribed conditions (Barratt, Cabak Rédei, Innes‐Ker, & van de Weijer, 2016; Calbi et al., 2017; Mobbs et al., 2006; Prince & Hensley, 1992). Hochberg and Brooks (1996, p. 265) explained why: “Despite Eisenstein's (1949) assertion that two pieces of film of any kind, when placed in juxtaposition, inevitably combine into a new concept of quality, there is no reason to believe that without specific effort at construal by the viewer anything other than a meaningless flight of visual fragments … will be perceived.” In other words, the filmmakers must first win over the viewer to the narrative and the diegetic world before any mind reading will link the separate shots (see also Cutting, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…But its shaky status does not undermine the power of the reaction shot, and the importance of a larger context (Calbi et al., 2017). As Barrett (2017), Bering (2002), and Zunshine (2012) have suggested, we do read faces in an obligatory manner, easily and sometimes wrongly imputing emotions and intentions—but we have to know and believe the context.…”
Section: Discussionmentioning
confidence: 99%
“…However, banks did not act illegally, but they exhibited a lack of morality. In fact, the causes of such severe crisis were not only economic, but also ethical; in this sense, we can consider individual moral failures, ethical failure related to management or governance, and social ethics failure [2].…”
Section: Introductionmentioning
confidence: 99%